Therapeutic approaches to chronic pain: Literature review - Avila, Diego Fernando de; Santos, Ana Cecília de Queiroz; Oliveira, Giovana Ribeiro de; Carnevali, Laura Stephany Ferreira; Garcia, Bruno Borges; Peres, Gabriel Francisco Ferrari; Júnior, Wesley Sidney dos Santos; Venâncio, Daniel Severino Soares; Ali, Alissa Khrais Hage; Ferreira, Gustavo de Oliveira (Seven Editora, 2024)
Introduction: Chronic pain is a complex and multifaceted condition, characterized by the persistence of pain beyond three months, as defined by the International Association for the Study of Pain (IASP). Unlike acute pain, chronic pain encompasses biological, psychological, and social factors, significantly affecting quality of life and daily functioning. Its diagnosis is challenging, often based on subjective descriptions of the patient, and requires a multidisciplinary approach for effective and personalized treatment. Objective: To analyze and synthesize the most recent research on chronic pain management strategies in order to identify the most effective treatment measures. Methodology: The searches were carried out in the PUBMED and LILACS databases, using the search process through vocabulary controlled through descriptors and Boolean operators "and" and "or". Conclusion: This review highlights the efficacy of various approaches in the management of chronic pain, from pharmacological treatments to physical and psychological therapies, emphasizing the need for multidisciplinary treatment. The challenges in diagnosis and personalized treatment, given the individual variability of chronic pain, are highlighted. The review also points out research gaps, the importance of psychosocial aspects, and the role of non-conventional therapies, concluding that chronic pain requires integrated and innovative therapeutic management. DOI:https://doi.org/10.56238/sevened2023.007-016